2019
DOI: 10.1158/1538-7445.sabcs18-gs2-04
|View full text |Cite
|
Sign up to set email alerts
|

Abstract GS2-04: Efficacy results from CIBOMA/2004-01_GEICAM/2003-11 study: A randomized phase III trial assessing adjuvant capecitabine after standard chemotherapy for patients with early triple negative breast cancer

Abstract: Background: Triple negative breast cancers (TNBC) have a greater risk of relapse than non-TNBC. New therapeutic approaches are needed for these patients (pts). CIBOMA/2004-01_GEICAM/2003-11 is a multinational, randomized phase III trial exploring adjuvant capecitabine (X) after completion of standard treatment in early TNBC pts. Materials and Methods: Patients with operable, node-positive (or node-negative with tumor size ≥ 1 cm), centrally confirmed hormone receptor-negative, HER2-negative earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
1
9
0
2
Order By: Relevance
“…This randomised phase 3 trial of 876 patients who had early-stage TNBC and who had completed standard adjuvant or neoadjuvant polychemotherapy was designed to analyse the impact of adjuvant capecitabine (1000 mg/m 2 from days 1 to 14, every 21 days) for all patients with TNBC regardless of their pCR status. There was no significant difference in 5-year DFS and OS between the treatment groups, highlighting the need to choose a treatment-resistant group 47 . The results of the CREATE-X trial now compel most clinicians to treat early-stage TNBC with neoadjuvant chemotherapy in order to understand who should have capecitabine.…”
Section: Managing Residual Disease Following Neoadjuvant Chemotherapymentioning
confidence: 88%
“…This randomised phase 3 trial of 876 patients who had early-stage TNBC and who had completed standard adjuvant or neoadjuvant polychemotherapy was designed to analyse the impact of adjuvant capecitabine (1000 mg/m 2 from days 1 to 14, every 21 days) for all patients with TNBC regardless of their pCR status. There was no significant difference in 5-year DFS and OS between the treatment groups, highlighting the need to choose a treatment-resistant group 47 . The results of the CREATE-X trial now compel most clinicians to treat early-stage TNBC with neoadjuvant chemotherapy in order to understand who should have capecitabine.…”
Section: Managing Residual Disease Following Neoadjuvant Chemotherapymentioning
confidence: 88%
“…A difference could be detected only in a subgroup with non-basal TNBC carcinomas (EGFR and CK5/6 negative) (p = 0.020, HR: 0.53 [95 % CI: 0.31, 0.91]). However, since the study was negative overall, it was also concluded in the subsequent discussion that, outside of the conditions in the Create-X study, the use of capecitabine is not indicated in patients with TNBC [69].…”
Section: Therapy For Primary Triple-negative Breast Cancermentioning
confidence: 99%
“…The CIBOMA/2004-01_GEICAM/2003-11 study was conducted in a different study setting but with the same question regarding modified therapy [69]. This study, which was conducted in Spain and Latin America, admitted triple-negative patients following adjuvant or neoadjuvant chemotherapy who received further treatment after completing therapy with capecitabine or who did not receive any further therapy.…”
Section: Therapy For Primary Triple-negative Breast Cancermentioning
confidence: 99%
“…The largest phase III trials that investigated the extended adjuvant mCTH in TNBC are CIBOMA 2004-01/GEICAM 2003-11 and SYSCBS-001 trials. In CIBOMA trial, the efficacy and safety of maintenance therapy of capecitabine were evaluated after primary treatment in patients with early stages TNBC (Martín et al, 2018), while in SYSCBS-001, capecitabine was evaluated as in CIBOMA studies but with different dose and duration Zhong-yu., NCT01112826). Also, the efficacy of extended therapy with capecitabine was evaluated in a famous phase III trial, the CREATE-X trial that showed a significant improvement in survival in patients with TNBC with a residual disease after neoadjuvant therapy (Masuda et al, 2017).…”
Section: Treatment Outcomementioning
confidence: 99%